Pretreatment with ethinylestradiol-drospirenone and metformin enhances ovulation and pregnancy in women with polycystic ovary syndrome - Laila, Rawnok; Nasif, T. M. Fahad; Munira, S. M.; Islam, Tahmida; Deeba, Farzana; Ishrat, Shakeela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Polycystic ovary syndrome (PCOS) is a major cause of anovulatory infertility and affects 5-10% women of reproductive age. High serum anti-mullerian hormone (AMH) is associated with lack of ovulation in PCOS women. Combined oral contraceptives containing ethinylestradiol and drospirenone suppress androgen production and reduce AMH concentration which may optimize the women with PCOS for better response to ovulation induction. This study aimed to assess the effects of ethinylestradiol-drospirenone (EE-DRSP) and metformin combination as pretreatment for ovulation induction in polycystic ovary syndrome in comparison to metformin only pretreatment. Methods: This was a randomized controlled trial conducted on a total 62 subfertile PCOS women having high serum AMH (≥5 ng/dl). They were randomly assigned into 2 groups. In group A 31 participants received EE-DRSP and metformin combination and in group B 31 participants received only metformin for 3 months. After 3 months the participants had ovulation induction with letrozole for 3 cycles. The outcome variables were the rates of ovulation and pregnancy. Results: Ovulation rate per cycle was higher in group A than group B. Cumulative ovulation rate per participant was also 1.36 times higher in group A than B (100.0% versus 73.3%). Cumulative pregnancy rate was 1.91 times higher in combination group than metformin alone group (67.7% versus 35.5%). Conclusions: Pretreatment with ethinylestradiol-drospirenone and metformin for three months before ovulation induction is more effective than metformin only in terms of higher ovulation and pregnancy rate in subfertile PCOS women.